2000
DOI: 10.1002/1097-0290(20000820)69:4<385::aid-bit5>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation kinetics of benzene, toluene, and phenol as single and mixed substrates forPseudomonas putida F1

Abstract: Although microbial growth on substrate mixtures is commonly encountered in bioremediation, wastewater treatment, and fermentation, mathematical modeling of mixed substrate kinetics has been limited. We report the kinetics of Pseudomonas putida F1 growing on benzene, toluene, phenol, and their mixtures, and compare mathematical models to describe these results. The three aromatics are each able to act as carbon and energy sources for this strain. Biodegradation rates were measured in batch cultivations followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
189
4
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 327 publications
(223 citation statements)
references
References 64 publications
25
189
4
5
Order By: Relevance
“…The µ max value is considerably lower than those determined for P. cepacia G4 (µ max = 0.30/h) by Schroeder et al (1997) from unstable steady state; P. putida ATCC17514 (µ max = 0.567/h) by Yang and Humphrey (1975) and P. aeruginosa (µ max = 0.152/h) by Agarry and Solomon (2008) from continuous cultivation. On the other hand, the value is comparable with the values obtained for P. putida F1 (µ max = 0.11/h) by Reardon et al (2000) and P. putida Q5 (µ max = 0.119/h) by Kotturi et al (1991) using batch cultivation. According to Layokun et al (1987) and Solomon et al (1994) growth of organism is a consequence of substrate consumption; hence the specific substrate (phenol) consumption rate (r s ) was calculated (as shown in Table 1) from the steady state data obtained for P.fluorescence.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The µ max value is considerably lower than those determined for P. cepacia G4 (µ max = 0.30/h) by Schroeder et al (1997) from unstable steady state; P. putida ATCC17514 (µ max = 0.567/h) by Yang and Humphrey (1975) and P. aeruginosa (µ max = 0.152/h) by Agarry and Solomon (2008) from continuous cultivation. On the other hand, the value is comparable with the values obtained for P. putida F1 (µ max = 0.11/h) by Reardon et al (2000) and P. putida Q5 (µ max = 0.119/h) by Kotturi et al (1991) using batch cultivation. According to Layokun et al (1987) and Solomon et al (1994) growth of organism is a consequence of substrate consumption; hence the specific substrate (phenol) consumption rate (r s ) was calculated (as shown in Table 1) from the steady state data obtained for P.fluorescence.…”
Section: Resultssupporting
confidence: 86%
“…Of these various models, the Monod and Andrew (Haldane) equations have been extensively used to describe phenol biodegradation (Bandyopadhyay et al, 1998;Oboirien et al, 2005;Reardon et al, 2000). The Monod and Andrew (Haldane) equations are based on the specific growth rate (Bandyopadhyay et al, 1998;Reardon et al, 2000), but may also be related to the specific substrate consumption rate (Edwards, 1970, Solomon et al, 1994.…”
Section: Introductionmentioning
confidence: 99%
“…The classical method of obtaining kinetic parameters (constants) is to linearize kinetic models. Recently, non-linear least squares computer fitting of data to model equations has been used (Schroeder et al, 1997;Reardon et al, 2000;Saravanan et al, 2008). The non-linear least square fitting routine of MATLAB 6.5 software package was used to fit the Monod kinetic model to the different batch experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of techniques involving physical, chemical and biological methods have been used for the removal of phenol from industrial effluents and contaminated The meta-cleavage pathway for the biodegradation of phenol A= Phenol, B= Catechol, C= 2-Hydroxymuconic semialdehyde, D= 2-Hydroxymuconate, E= 2-Oxo-4-enoadipate, F= 2-Oxo-penta-4-enoate, G= Pyruvate, H= Acetaldehyde, I= Acetyl Co A, E1= Monooxygenase phenol hydroxylase, E2=Catechol-2, 3-dioxygenase, E3= Hydrolase, E4= Dehydrogenase, E5= Isomerase, E6= Decarboxylase, E7= Hydrotase, E8= Aldolase waters with bioremediation receiving the most attention due to its environmental friendliness, its, ability to completely mineralize toxic organic compounds and of low-cost (Kobayashi and Rittman, 1982;Prpich and Daugulis, 2005). Microbial degradation of phenol with different initial concentrations ranging from 50-2000 mg/L have been actively studied using shake flask, fluidized-bed reactor, continuous stirred tank bioreactor, multistage bubble column reactor, air-lift fermenter and two phase partitioning bioreactor methods (Bettmann and Rehm, 1984;Sokol, 1988;Annadurai et al, 2000;Reardon et al, 2000;Ruiz-ordaz et al, 2001;Oboirien et al, 2005;Prpich and Daugulis, 2005;Saravanan et al, 2008) and these studies have shown that phenol can be aerobically degraded by wide variety of fungi and bacteria cultures such as Candida tropicalis (Ruiz-ordaz et al, 2001, Chang et al, 1998Ruiz-ordaz et al, 1998); Acinetobacter calcoaceticus (Paller et al, 1995); Alcaligenes eutrophus (Hughes et al, 1984;Leonard and Lindley, 1998); Pseudomonas putida (Hill and Robinson, 1975;Kotturi et al, 1991;Nikakhtari and Hill, 2006); and Burkholderia cepacia G4 (Folsom et al,1990, Solomon et al,1994. In microbial degradation of phenol under aerobic conditions, the degradation is initiated by oxygenation in which the aromatic ring is initially monohydroxylated by a mono oxygenase phenol hydroxylase at a position ortho to the pre-existing hydroxyl group to form catechol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation